2014
DOI: 10.1016/j.enpol.2013.12.046
|View full text |Cite
|
Sign up to set email alerts
|

Micro-hydro power in the UK: The role of communities in an emerging energy resource

Abstract: Further information on publisher's website:http://dx.doi.org/10. 1016/j.enpol.2013.12.046 Publisher's copyright statement: NOTICE: this is the author's version of a work that was accepted for publication in Energy policy. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be re ected in this document. Changes may have been made to this work since it was submitted for publication. A de nitive version wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 32 publications
(40 reference statements)
1
21
0
1
Order By: Relevance
“…This percentage represents the 14% of the renewable electricity generated in the country. According to a study that was carried out by Bracken et al [5], hydropower projects that have been realized in the UK are, in most of the cases, for small scale energy production (less than 100,000 kWh/yea r). In the last years, the number of micro-hydro plants (up to 5 MW installed capacity) increased due to the high efficiency and low costs, mainly in rural areas and small communities [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This percentage represents the 14% of the renewable electricity generated in the country. According to a study that was carried out by Bracken et al [5], hydropower projects that have been realized in the UK are, in most of the cases, for small scale energy production (less than 100,000 kWh/yea r). In the last years, the number of micro-hydro plants (up to 5 MW installed capacity) increased due to the high efficiency and low costs, mainly in rural areas and small communities [6].…”
Section: Introductionmentioning
confidence: 99%
“…As regards the cost of installation, Paish [1] found that, for small plants up to 500 kW, the costs could vary in a wide range, due to the characteristics of the site; nevertheless, using local expertise and technologies can minimize these costs. Bracken et al [5] stated that, probably, more than other community-based renewable resources, the costs of small hydropower plants tend to be very dependent on local conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Kritisch, reflexiv und erkundend werden immer wieder Fragen nach Beiträgen der Sozialwissenschaften zur Energieforschung thematisiert (Shippee 1981, Rochlin 2014, Ryan/Hebdon/Dafoe 2014, was oft auch eine Forderung der Integration der Sozialwissenschaften in die Energieforschung miteinschließt . Weitere Beispiele für das Zusammenwirken von sozialen und ökologisch-naturwissenschaftlichen Einflussfaktoren finden sich im Kontext von mariner Energienutzung (Bonar/ Bryden/Borthwick 2015) oder hinsichtlich der Bedeutung von Communities im Wasserkraft-Sektor (Bracken/Bulkeley/Maynard 2014) . 2015, Trachtenberg 2015a, dekonstruktivistische Perspektiven hinsichtlich der Entzauberung von Energie-Fakten entwickelt (Sovacool/Brown 2015) sowie Verbindungen der Sozialwissenschaften zur Energiepolitik hergestellt (Stirling 2014) .…”
Section: Konkreter Untersuchungsansatzunclassified
“…that it is costly, that loss of control may occur, Irvin and Stansbury, ) or about the communities themselves (e.g. lack of knowledge) tend to reduce community involvement to a one‐way delivery of information (Thomas, ) and thus increase the importance of technical approaches, ignoring social and community input (Bracken, Bulkeley, & Maynard, ). Given the asymmetry of power between the two parties involved, it is extremely important to understand experts’ barriers to community engagement.…”
Section: Introductionmentioning
confidence: 99%